Modulating T Cell Activation Using Depth Sensing Topographic Cues. Issue 9 (3rd August 2020) - Chaudhuri, Parthiv Kant; Wang, Mitchell S.; Black, Charles T.; Huse, Morgan; Kam, Lance C.
Abstract: This report examines how sensing of substrate topography can be used to modulate T cell activation, a key coordinating step in the adaptive immune response. Inspired by the native T cell–antigen presenting cell interface, micrometer scale pits with varying depth are fabricated into planar substrates. Primary CD4 + T cells extend actin‐rich protrusions into the micropits. T cell activation, reflected in secretion of cytokines interleukin‐2 and interferon gamma, is sensitive to the micropit depth. Surprisingly, arrays of micropits with 4 μm depth enhance activation compared to flat substrates but deeper micropits are less effective at increasing cell response, revealing a biphasic dependence in activation as a function of feature dimensions. Inhibition of cell contractility abrogates the enhanced activation associated with the micropits. In conclusion, this report demonstrates that the 3D, microscale topography can be used to enhance T cell activation, an ability that most directly can be used to improve production of these cells for immunotherapy. Abstract : Immune cell activation using biomaterials can be leveraged to direct immune response. T cell activation can be regulated by depth of microscale topographies of an activating surface. This report highlights the importance of the topographic cues in T cell activation suggesting a strategy for gaining greater control over the response of cells of the adaptive immune system to biomaterials.